Copper(I)‐Catalyzed One‐Pot Synthesis of Highly Functionalized Pyrrolidines from Sulfonyl Azides, Alkynes, and Dimethyl 2‐(Phenylamino)maleate. Issue 3 (12th December 2014) - Ramanathan, Devenderan; Pitchumani, Kasi
Abstract: An efficient one‐pot synthesis of highly functionalized pyrrolidines by using sulfonyl azides, alkynes, and dimethyl 2‐(phenylamino)maleate catalyzed by copper(I)–Y zeolite under mild reaction conditions was investigated. This cascade process involves an azide–alkyne [3+2] cycloaddition/ring rearrangement/ketenimine formation/intermolecular nucleophilic addition cascade and consequent intramolecular cyclization followed by [1, 3]‐H shift. The important advantage of this methodology, which allows selective intramolecular nucleophilic attack of the generated ketenimine carbanion on an ester moiety for the first time, is that the starting materials can be easily prepared. Abstract : A cascade process involving a copper‐catalyzed azide–alkyne [3+2] cycloaddition/ring rearrangement/ketenimine formation/intermolecular nucleophilic addition sequence and consequent intramolecular cyclization followed by [1, 3]‐H shift is reported.